Articulação entre Paulo Freire e Herbert Marcuse para uma educação sexual humanizadora - Demartini, Gabriel Ribeiro (2015)
This work originated from previous investigations into a liberating curriculum development perspective in teaching about science teenage pregnancy by Freire's thematic approach. Once perceived the production of drive (trieb) poverty within their own science teaching, commonly associated with restrictive and biologist visions of sexuality, this study sought to build from previous investigations, presenting as research problem the following interrogative: to what extent teaching practices on sexuality, values and meanings can be a limiting humanizing conception on the theme and how critical pedagogy can help overcome this limitation? The idea was to build a theoretical chaining able to subsidize humanizing practices on sex education. For this, Herbert Marcuse s thought was used articulated to Paulo Freire s educational thought. In order to illustrate the theoretical development, an exploratory approach to the educational reality was searched through the analysis of Sexual Prevention Project developed at the state school John Climaco de Camargo Pires in Sorocaba-SP, using for that, document analysis, participant observation and semi-structured interviews. From the built theoretical articulation, three categories of analysis were formulated: emancipatory drive, critical sensitivity and aesthetics of Liberating Education. In synthesis, they discourse about the instinctual gratification opportunities through the break with lucrative rationality present in capitalist society. From a new rationality, linked to a new sensibility, focused on the life s promotion to glimpse the possibility of overcoming the rationality of domination. Within the sexual education, from an aesthetic conceiving defined in dialogicity, it was looked for a sensitive perception in the face of situations of dehumanization. Thus, the pedagogical practice about sex education in science teaching should provide sensitive perception of power for freedom via aesthetic dimension and awakening the need and the possibility of social and individual emancipation. Analysis of the Sexual Prevention Project allowed the perception of the overcome process failure of the restricted perspectives on sex education, being recurrent biologist approaches. As a possibility of overcoming and direction for a humanizing sex education, aesthetically, ethically and politically engaged, the perspective of curriculum development, via generating theme, is presented as a sociocultural construct with opportunities to put the subjects in praxiological movement for its humanization.